PHILOLOGICAL AND METHODOLOGICAL NECESSITIES OF TEACHING WESTERN LITERATURE TO UZBEK PUPILS - Bekturdiyeva, Guli (INTERNATIONAL CONFERENCES, 2023)
Studying literature enhances our understanding of how we communicate, shape our identities and understand the world, both in the present and the past. It enables us to envisage the future and its possibilities, enriches our understanding of identity, citizenship and culture, inviting us to think imaginatively about these matters and to explore the forms in which they may be communicated.